Oral Administration of Resveratrol Alleviates Osteoarthritis Pathology in C57BL/6J Mice Model Induced by a High-Fat Diet - Mengqi Jiang; Xingyao Li; Xiaolu Yu; Xudan Liu; Xiaolei Xu; Jianyi He; Hailun Gu; Li Liu (Mediators of Inflammation)
Obesity has been associated with osteoarthritis (OA) due to increased mass and metabolic factors which are independent of the biomechanical contribution to joint load. Resveratrol, a natural polyphenolic compound, exerts protective effects on OA through its anti-inflammatory property. However, the mechanism of resveratrol on obesity-related OA is unclear. To investigate the effect and possible mechanism of oral resveratrol on obesity-related OA, we fed C57BL/6J mice with a high-fat diet (HFD) for 16 weeks to establish obesity-related OA model; then two doses (22.5 mg/kg and 45 mg/kg) of resveratrol were given by gavage for additional 12 weeks. Mice with HFD significantly increased body weights compared to the control mice, while resveratrol treatment did not cause obvious weight loss. Histological assessments showed that resveratrol at 45 mg/kg significantly improved OA symptoms. Levels of serum IL-1β and leptin were decreased by resveratrol treatment and positively correlated with Mankin scores. Moreover, resveratrol significantly inhibited the expression of TLR4 and TRAF6 in cartilage. These results suggest that HFD induced obesity can lead to the occurrence of OA, and resveratrol may alleviate OA pathology by decreasing the levels of systematic inflammation and/or inhibiting TLR4 signaling pathway in cartilage. Thus, resveratrol might be a promising therapeutic treatment for obesity-related OA.